Pelaksanaan Pengadaan Tanah Untuk Pembangunan Jalan Tol Yogyakarta - Solo Di Kabupaten Boyolali (Studi Kasus Pembangunan Jalan Tol Kulon Progo Yogyakarta-Solo) - Rachma Zaini Winarda; Joko Mardiyanto; Nanik Sutarni (Fakultas Hukum Universitas Boyolali, 2021)
Abstract : The aim of this study is to work out The implementation of land acquisition for development, specifically in Boyolali Regency. The implementation of land acquisition aims to make sure the supply of land for development within the public interest in Indonesia as stipulated in Law Number 2 of 2012 concerning Land Procurement for Development within the Public Interest. The approach method used is empirical juridical, the sort of research may be a qualitative approach. Methods of knowledge collection using interviews, literature study and documentation. the tactic used is data analysis by collecting the info obtained. The stages in land acquisition include: drawing board , preparation stage, implementation stage, and yield submission stage. The implementation of land acquisition for road construction includes inventory and identification of tenure , ownership, and utilization, compensation assessment, deliberation on compensation determination, granting compensation, and disposal of village treasury land; obstacles and solutions: within the measurement using village drawings that are still not accurate, they're replaced with the newest method, namely using digital measuring instruments in order that the calculation of the world is more accurate. the necessity for coordination between Task Force A, Task Force B, village officials. The calculation of compensation by the Assessment Team is decided consistent with the points and consistent with the identification data from the nominative data in order that if there are community members who don't accept as true with the worth of the land value, a consignment are often administered .The conclusion of this study states that the implementation of land acquisition for development is in accordance with Law No. 2 of 2012 and Presidential Regulation No. 19 of 2021. The community must understand the stages in land acquisition and compensation and supply socialization of the legal basis for land acquisition, Unite and achieve an agreement on perceptions between residents and therefore the government regarding the worth of the land price. Abstrak : Tujuan penelitian ini untuk mengetahui pelaksanaan pengadaan tanah bagi pembangunan khususnya di Kabupaten Boyolali. Pelaksanaan pengadaan tanah bertujuan untuk menjamin ketersediaan tanah untuk pembangunan bagi kepentingan umum di Indonesia tertuang dalam Undang – Undang yang Nomor 2 Tahun 2012 berisi tentang Pengadaan Tanah Bagi Pembangunan Bagi Kepentingan Umum. Metode pendekatan yang digunakan yuridis empiris, jenis penelitiannya pendekatan kualitatif. Metode pengumpulan datanya menggunakan wawancara, studi pustaka dan dokumentasi. Metode yang digunakan analisis data dengan menghimpun keseluruhandata yang diperoleh.Tahapan dalam pengadaan tanah antara lain : tahapan perencanaan, tahapan persiapan, tahapan pelaksanaan, tahapan penyerahan hasil. Tata cara pengadaan tanah untuk pembangunan jalan tol meliputi Inventarisasi serta identifikasi penguasaan, pemilikan, dan pemanfaatan tanah, penilaian ganti rugi, musyawarah penetapan untuk ganti kerugian, pemberian hak ganti rugi, dan pelepasan tanah kas desa; hambatan dan penyelesaian: didalam pengukuran menggunakan sket gambar desa yang masih manual belum akurat digantikan dengan metode terbaru yaitu menggunakan alat ukur digital sehingga perhitungan luasnya lebih akurat. Perlunya koordinasi antara Satgas A, Satgas B, perangkat desa.. Perhitungan ganti rugi oleh Tim Penilai yang ditentukan sesuai poin – poin dan sesuai data identifikasi dari data nominatif sehingga jika ada warga masyarakat tidak setuju dengan harga nilai tanah maka dapat dilakukan konsinyasi. Kesimpulan dari penelitian ini menyebutkan bahwa tahap pengadaan tanah untuk pembangunan sudah sesuai dengan Undang – Undang Nomor 2 tahun 2012 dan Peraturan Presiden Nomor 19 Tahun 2021.Masyarakat harus memahami tahapan dalam pengadaan tanah dan ganti rugi serta memberikan sosialisasi dasar hukum pengadaan tanah, Menyatukan dan mencapai kesepakatan tentang persepsi antara warga dengan pemerintah mengenai nilai harga tanah yang diganti rugi.